THE CHARACTERISTICS OF HUMAN IMMUNODEFICIENCY VIRUS/ACQUIRED IMMUNODEFICIENCY SYNDROME PATIENTS IN RSUP PROF. Dr. I.G.N.G. IN 2021 - Tunicha Goranatha, Made Bagus; Subawa, A. A. Ngurah; Herawati, Sianny; Mulyantari, Ni Kadek (E-Jurnal Medika Udayana; Vol 14 No 03 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i3.P09, 2025)
HIV/AIDS is a term coined for a particular disease that attacks human immune system. The infected of HIV/AIDS, which will be called patient from this point, also tends to suffer from complication of various other diseases, of which potentially could lead to death. HIV/AIDS is categorized into Sexually Transmitted Disease (STD) due to the reason that the disease is spread through sexual contact. That is why this research study is conducted in order to explore, and investigate the characteristics of the HIV/AIDS patients so that the obtained result can be used as reference for clinical practitioner. This research study uses descriptive retrospective approach with cross-sectional method where the data collection is proceeded by observing many subjects at one point of time. Data is obtained from medical record through data collecting method used on this study which is called total sampling. This research study result in founding 91 patients, with highest number distribution of patients is at age > 35 years old, as many as 56 patients (61.5%), the sex consisted of mostly male sex as many as 62 patients (68.1%), the job is mostly consisted of corporate workers as many as 47 patients (51.6%), for the education is mostly founded those of High School as many as 65 patients (71.4%), followed by marriage status is mostly consisted of those who have married as many as 69 patients (75.8%). HIV/AIDS patients are found, mostly consisted from the age > 35 years old, with sex of male sex, for the occupation is from corporate worker, for the education is from Senior High School, and infection causality spread through heterosexual sexual contact. HIV/AIDS, ages. Sex, occupation, marriage status, infection causality.